Improving the Safety and Continuity Of Medicines management at Transitions of care (ISCOMAT): protocol for a process evaluation of a cluster randomised control trial - Chris P Gale; Ian Kellar; Beth Fylan; Hanif Ismail; Liz Breen; Peter Gardner; Jon Silcock; Roberta Longo; Robert Turner; John Wright; Catherine Powell; Chris Bojke; et al. (BMJ Open, 2020)
Introduction A key priority for the UK National Health Service and patients is to ensure that medicines are used safely and effectively. However, medication changes are not always optimally communicated and implemented when patients transfer from hospital into community settings. Heart failure is a common reason for admission to hospital. Patients with heart failure have a high burden of morbidity, mortality and complex pharmacotherapeutic regimens. The Improving the Safety and Continuity Of Medicines management at Transitions of care programme comprises a cluster randomised controlled trial which will test the effectiveness of a complex behavioural intervention aimed at improving medications management at the interface between hospitals discharge and community care. We will conduct a rigorous process evaluation to inform interpretation of the trial findings, inform implementation of the intervention on a wider scale and aid dissemination of the intervention.Methods and analysis The process evaluation will be conducted in six purposively selected intervention sites (ie, hospital trusts and associated community pharmacies) using a mixed-methods design. Fidelity and barriers/enablers of implementation of the Medicines at Transitions Intervention (MaTI) will be explored using observation, interviews (20 patients, 40 healthcare professionals), surveys and routine trial data collection on adherence to MaTI. A parallel mixed analysis will be applied. Qualitative data will be thematically analysed using Framework analysis and survey data will be analysed descriptively. Data will be synthesised, triangulated and mapped to the Consolidated Framework for Implementation Research where appropriate. The process evaluation commenced on June 2018 and is due to end on February 2021.Ethics and dissemination Approved by Research Ethics Committee and the UK Health Research Authority REC: 18/YH/0017/IRAS: 231 431. Findings will be disseminated via academic and policy conferences, peer-reviewed publications and social media.Trial registration number ISRCTN66212970.